Penyuluhan Tentang Pentingnya Memilih Jajanan Sehat Terhadap Pengetahuan Anak di Sekolah Dasar Negeri 04 Tengguli - Fitriani; Lusi Lestari; Listari; Wahdah; Ega Aprisa; Uray Shelli; Ramzi; Angga Saputra; Rona Safrina; Amira; Isa Mufida; Rosa Amelia; Rizki Hastuti; Aswitri; Azura; Nur Hikmah; Noviyanti; Melin; Rahmawati (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2022)
Snacks are foods that can be consumed instantly and are liked by adults and children alike. Most children really like snacks because they like snacks with various shapes, striking colors and good taste. Therefore, the purpose of this counseling was to provide an understanding of how to choose healthy snacks at the 04 Tengguli Elementary School in Tengguli, Sajad District, Sambas Regency, West Kalimantan. The approach used in this activity includes a model of material exposure, educational games, and evaluation. The counseling activities carried out went smoothly, it could be seen that the elementary school students were enthusiastic in participating in the activities from beginning to end. This counseling is expected to provide education to students, especially students of SDN 04 Tengguli so that they can distinguish between healthy snacks and unhealthy snacks, besides that students are also expected to understand the impact of consuming unhealthy snacks.